PEMANFAATAN BAHAN ORGANIK SEBAGAI CAMPURAN MEDIA PEMBIBITAN SETEK LADA - SAFITRI, MARIA ANDANI; SAFWAN, MULYADI; ANGGOROWATI, DINI (Jurnal Sains Pertanian Equator, 2018)
ABSTRACTPepper (Piper nigrum Linn) is an important spice plant that can"™t be replaced with other herbs, especially in Indonesia. However, productivity and production is currently low due to the large number of trees being felled and replaced with oil palm and rubber, whereas the demand for these commodities is still high in the form of white pepper and black pepper, therefore pepper cultivation in West Kalimantan is still very promising but it must be done improvement of pepper cultivation technique especially since from breeding. This study aims to determine the organic material that provides the best growth as a mixture of pepper cuttings breeding the place. This research was conducted in Pontianak, street parit Demang road for 4 months from August 28th 2017 to January 2nd2018. The study used a Completely Randomized Design (RAL) design, consisting of 4 replication treatments 6 and plant samples 5. Observational variables included live percentage, plant height, number of leaves, root volume, shoot dry weight, root dry weight and environmental observation. The results showed that the utilization of organic material as a mixture of pepper cuttings nursery media has no significant effect on all observation variables. Based on the research done it can be concluded that all organic materials used as a mixture of media can provide the same growth of pepper cuttings nursery. Keywords: Nursery Media of Pepper Cuttings, Papper.